Exploring vocabulary learning needs and preferred media among fifth-grade English as a foreign language learners - Talan, Scolastica Eva; Yulia, Yuyun; Hidayati, Sari (UPT Bahasa Universitas Tanjungpura, 2025)
This study aims to analyze the target needs and learning needs of the EFL students of Fifth-Grade Elementary Students in Yogyakarta. The innovation of this research lies in employing survey questionnaire, interview, and observation to provide an in-depth analysis regarding vocabulary learning among elementary EFL students. The participants in the study are 29 students and 2 teachers. Employing explanatory sequential design, the data collected were analyzed using descriptive quantitative and thematic qualitative methods to better understand the results and draw meaningful conclusions about the student’s learning preferences. The findings indicate that the students find it difficult to acquire new English vocabulary and tend to ask their teachers what the words’ meanings are. The survey questionnaire revealed that the students prefer pair or group activities rather than individual activities indicating a preference for peer support in the learning process. They like to visualize learning by using pictures, videos, and flashcards as it helps them to memorize new vocabulary. From the interview with the teachers, it became evident that there is a need for supplementary instructional materials that incorporate group work, engaging learning media, and the use of Information Communication and Technology (ICT) to enhance students’ vocabulary mastery. In conclusion, the study recommends a student-centered approach by combining group work and interesting learning media to enrich students’ vocabulary acquisition. Keywords: Group-work; ICT; materials; need analysis; vocabulary